2015
DOI: 10.1021/acs.macromol.5b01423
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydrophobic Moieties in Water-Soluble Polymers on Physical Exfoliation of Graphene

Abstract: Graphene is a fascinating material with unique properties, such as high mechanical strength and excellent electronic and thermal conductivities, as well as many other beneficial properties. Despite much recent effort, the facile synthesis and colloidal stabilization of graphene in aqueous solutions remains central to both academic research and practical applications. Here, we provide an in-depth insight into how the hydrophobic moieties of polymers affect the physical exfoliation of graphite into graphenes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 45 publications
1
31
0
2
Order By: Relevance
“…Over the past years, it has been proven that graphene can be dispersed in water by using a wide range of polymers acting as DSAs, [14,195,197,198,[215][216][217][223][224][225][226][227][228][229][230][231][232] such as cellulose acetate (CA), [233] ethyl cellulose (EC), [229] polyvinylpyrrolidone (PVP), [224] lignin, [230] gum arabic (GA), [225,226] gelatin derived from animal skin and bones, [227] and even more complex systems such as bovine serum albumin (BSA), [223] hyaluronan (PyHA) [216] and DNA [198] functionalized with pyrene head-groups.…”
Section: Polymers As Dsasmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past years, it has been proven that graphene can be dispersed in water by using a wide range of polymers acting as DSAs, [14,195,197,198,[215][216][217][223][224][225][226][227][228][229][230][231][232] such as cellulose acetate (CA), [233] ethyl cellulose (EC), [229] polyvinylpyrrolidone (PVP), [224] lignin, [230] gum arabic (GA), [225,226] gelatin derived from animal skin and bones, [227] and even more complex systems such as bovine serum albumin (BSA), [223] hyaluronan (PyHA) [216] and DNA [198] functionalized with pyrene head-groups.…”
Section: Polymers As Dsasmentioning
confidence: 99%
“…In this framework, Yoon and co-workers have shown that graphene dispersions can be stabilized by four different polymers based on either poly(vinyl alcohol) (PVA) or dextran functionalized with conjugated moieties, such as phenyl or pyrene (see PyDT and PyPVA in Figure 10). [217] The ability of these polymers to stabilize graphene dispersions was systematically investigated. Moreover, graphene hydrogels and aerogels were prepared from the aqueous dispersion of the graphene/polymer.…”
Section: Reviewmentioning
confidence: 99%
“…In any case, the strong polymer/graphene interactions make extremely difficult to separate the produced composites, which in some cases resulted in interesting materials. In this connection, Yoon and co-workers produced stable graphene dispersions by simply sonicating graphite with four different polymers based on either poly(vinyl alcohol) (PVA) or dextran 123. The water-soluble polymers with phenyl-and pyrenyl-functionalized side chains facilitated the formation of stable aqueous dispersions of graphene without degrading its sp 2 hybridized structure.…”
mentioning
confidence: 99%
“…The chemical structures of such polymers can be modified for the aqueous dispersion of 2D nanomaterials. A recent work reported the synthesis of four different polymer derivatives by using two well‐known water‐soluble polymers, PVA and DT, for the physical exfoliation of graphite in aqueous solutions . PVA and DT were chosen owing to their ability to disperse single‐walled carbon nanotubes in aqueous solutions.…”
Section: Exfoliation Approachesmentioning
confidence: 99%